2021
DOI: 10.1016/j.ajic.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis investigating the relationship between clinical features, outcomes, and severity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia

Abstract: Objective: We aimed to investigate the relationship between clinical characteristics, outcomes and the severity of severe acute respiratory syndrome coronavirus 2 pneumonia. Methods: We performed a systematic review and meta-analysis using PubMed, Embase, and Cochrane Library databases to assess the clinical characteristics and outcomes of confirmed COVID-19 cases and compared severe (ICU) and nonsevere (non-ICU) groups. Results: We included 12 cohort studies including 2,445 patients with COVID-19. Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
118
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 21 publications
18
118
2
9
Order By: Relevance
“…This could be due to the fact that more educated peoples have more knowledge about the disease and the recommended prevention strategies. COVID-19 severe clinical disease and death have been reported mainly in peoples with advanced age and patients who had chronic disease concomitantly (11,18). In our study, an independent association was observed between young adults and low perceived e cacy of COVID-19 prevention methods.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…This could be due to the fact that more educated peoples have more knowledge about the disease and the recommended prevention strategies. COVID-19 severe clinical disease and death have been reported mainly in peoples with advanced age and patients who had chronic disease concomitantly (11,18). In our study, an independent association was observed between young adults and low perceived e cacy of COVID-19 prevention methods.…”
Section: Discussionsupporting
confidence: 54%
“…In our context, though not studied, one of the main reasons could be related to wrong perception of people towards the disease and the recommended prevention measures. Studies revealed that severity of COVID-19 was found to be high in patients who had chronic disease concomitantly (11,18). Thus, patients who have been living with chronic diseases should perceive as they are the most vulnerable group of peoples to COVID-19 and as much as possible they should carry out all the recommended protective measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature above 38°5 C at admission was also associated with a poor outcome in our cohort. We studied this variable, already described as a prognostic factor in COVID-19 (16,17), and especially as hyponatremia may be associated with fever. We found signi cant association between these two variables, but after multivariate analysis, only hyponatremia remains an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%